KESESUAIAN PERTIMBANGAN HAKIM DALAM PEMIDANAAN TERHADAP TERDAKWA ANAK DENGAN PERATURAN PERUNDANG-UNDANGAN YANG BERLAKU - Wulandari, Ulinda Sekar; Kristiyadi, Kristiyadi (Verstek, 2023)
This study aims to determine the suitability of the judge's consideration in the Decision of the Klaten District Court Number 3/Pid.Sus-Child/PN.Kln with the provisions of the applicable laws, especially Law Number 11 of 2012 concerning the Criminal Justice System of Children. This study uses prescriptive normative legal research methods. This study uses a case study. The types of legal materials used include primary and secondary legal materials. The legal material collection technique used by the authors in this study is a document study technique or library research. The legal material analysis technique in this study uses the syllogism method with the mindset of deduction. The results showed that the judge's consideration was based on the indictment of the Public Prosecutor and Juridical and Non-juridical considerations in imposing a criminal supervision to children in the form of placing children under the supervision of the public prosecutor for 3 (three) months in accordance with applicable laws and regulations. In its consideration, the judge had considered at least two pieces of evidence, namely witness statements and the defendant's statement where the beliefs obtained from the two evidences the judge was able to state that the defendant had been guilty of committing the criminal acts of theft by weighting. Keywords: Judge's consideration, Child, Theft of Crimes, Criminal Imposition